Redesigning the Institutional Framework of Indonesia’s Truth and Reconciliation Commission: Penataan Ulang Kerangka Kelembagaan Komisi Kebenaran dan Rekonsiliasi Indonesia - Yusuf, Muhammad Rifai; Rizqiyanto, Naufal; Sangadji, Sulastri (Lex Renaissance, 2025)
TRCs are globally recognized as one of the means to resolve past gross human rights violations. As a country that has transitioned from an authoritarian to a democratic regime, Indonesia has committed to resolving the issue. One progressive effort was the enactment of Law No. 27 of 2004 on the Truth and Reconciliation Commission. However, the Law no longer applies after it was annuled by Indonesian Constitutional Court so that the commission has no normative basis at the law under the Constitution. This research seeks to answer three main problems, first, how the TRC is viewed by international law and the Indonesian constitutional system. Second, how are the dynamics of its arrangement in Indonesia. Third, what kind of ideal institutional design can be offered. This study used normative legal research with statutory, conceptual, and historical approaches to explain the problems and. The result shows that first, TRCs is consistent with the Indonesian constitutional system. Second, the ratio decidendi of the annulment of the TRC Law by the Constitutional Court because it does not guarantee justice for victims of past gross human rights violations. Third, several aspects that need to be redesigned from the new institutional model of a constitutional TRC are related to institutions, members, mechanisms for providing justice for victims, including amnesty for perpetrators and the opening of opportunities for appeals to a human rights court.